2012
DOI: 10.1111/j.1365-2591.2012.02083.x
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivity of EndoSequence Root Repair Material and Bioaggregate

Abstract: Exposure of MTA, BA and ERRM to PBS resulted in precipitation of apatite crystalline structures that increased over time. This suggests that the tested materials are bioactive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
110
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(123 citation statements)
references
References 33 publications
9
110
0
4
Order By: Relevance
“…The setting reaction begins in the presence of moisture. Previous studies have demonstrated that ERRM is a biocompatible 15 and bioactive material 16 that has sealing ability, 17 antibacterial activity, 18 and compressive strength, 19 similar to PMTA.…”
Section: 5005/jp-journals-10024-2033mentioning
confidence: 99%
“…The setting reaction begins in the presence of moisture. Previous studies have demonstrated that ERRM is a biocompatible 15 and bioactive material 16 that has sealing ability, 17 antibacterial activity, 18 and compressive strength, 19 similar to PMTA.…”
Section: 5005/jp-journals-10024-2033mentioning
confidence: 99%
“…This process proves the bioactivity of CEM. Shokouhinejad et al [25] compared the performance of BioAggregate, EndoSequence and MTA when exposed to PBS. It resulted in the precipitation of apatite crystals that increased over time at the surface of all the tested materials, which suggests their bioactivity.…”
Section: Biological Properties Bioactivitymentioning
confidence: 99%
“…A bioactive material is able to interact with living tissues, resulting in biomineralization at the material-tissue interface [25], thus leading to regeneration and healing. Biodentine was proved to be bioactive by measuring the amount of calcium and silicone ions and carbonate incorporated from the material to the adjacent dentin in the presence of PBS (phosphate-buffered solution).…”
Section: Biological Properties Bioactivitymentioning
confidence: 99%
“…47 The material is nanofilled, allowing good adaptation to the root canal and flow into open dentinal tubules.…”
Section: Dentalmaterialsmentioning
confidence: 99%
“…The material has the ability to form surface apatite crystals that help contribute to bioactivity. 47 It has a long setting time (1260 min), low washout and mechanical properties (compressive strength 16.34 MPa, Vickers hardness 10.7) and high fluid uptake and water sorption. 55 Biodentine TM (Septodont, Saint…”
Section: Other Calcium Silicate Materialsmentioning
confidence: 99%